BETA Language Development: Survey Report, 1. November 1976 - Kristensen, Bent Bruun; Madsen, Ole Lehrmann; Nygaard, Kristen (DAIMI Report Series, 1977)
The report describes ongoing work within the Joint Language Project (JLP). Research workers from Aarhus aned Aalborg Universities. Denmark and the Norwegian Computing Center, Oslo, Norway participate in the project. The aim of the JLP is to consider new tools in programming by the development of a systems programming language BETA and a high level programming language GAMMA, both related to the system description language DELTA. The present state of the ideas for BETA is presented. This report is also referred to as DELTA Project Working Note No. 3.